Pengaruh Keterampilan, Pengetahuan dan Karakter Pada Tingkat Profesionalisme Dosen di Perguruan Tinggi - Abiana, I Gusti Ngurah; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2019)
Professionalism is a trait, skill, and way of implementing things done by a professional. A  lecturer is absolutely in need of sufficient professionalism because there is a demand,  especially the accounting lecturer that if the lecturer is not professional it will produce  accountants who are also unprofessional. The purpose of this study was to analyze the  influence of skills, knowledge, and character on student perceptions of the professionalism of  lecturers. The sample of this study is accounting students, Faculty of Economics and  Business, Udayana University, with 171 respondents. This study uses a stratified random  sampling method and data collection using a questionnaire. Data is analyzed using multiple  linear regression analysis. The results of the analysis show that the skill, knowledge, and  character have a positive effect and on the students' perceptions of the lecturers  professionalism. Keywords:  Skills, knowledge, character, professionalism.